2020
DOI: 10.3238/arztebl.2020.0575
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin and Mineral Status in a Vegan Diet

Abstract: Background: In Germany, public interest in a vegan diet is steadily growing. There are, however, no current data on the macro-and micronutrient status of vegans.Methods: In a cross-sectional study entitled "The Risks and Benefits of a Vegan Diet" (RBVD), we investigated the dietary intake, basic laboratory parameters, vitamin status, and trace-element status of 36 vegans and 36 persons on an omnivorous diet. Each group consisted of 18 men and 18 women aged 30-60.Results: Nearly all the vegans and one-third of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
91
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(136 citation statements)
references
References 29 publications
20
91
2
7
Order By: Relevance
“…However, a sensitivity analysis revealed no change in the results after an adjustment for the month of blood collection. In agreement with the current evidence, the dietary intake of vitamin D3 is lower in vegans [21], but we observed no difference in the vitamin D3 blood concentrations between vegans and omnivores, most likely because 50.0% of our vegans took vitamin D3 supplements.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, a sensitivity analysis revealed no change in the results after an adjustment for the month of blood collection. In agreement with the current evidence, the dietary intake of vitamin D3 is lower in vegans [21], but we observed no difference in the vitamin D3 blood concentrations between vegans and omnivores, most likely because 50.0% of our vegans took vitamin D3 supplements.…”
Section: Discussionsupporting
confidence: 92%
“…Next to vitamin B12, the results of this review suggest a protective role of vitamins B2 and B6 in bone health [13]. Interestingly, in agreement with the reduced bone health of vegans in the RBVD study, we also observed lower plasma concentrations of vitamin B2 in vegans, which is explained by the lower dietary intake compared to omnivores [21]. Indeed, a few studies have shown that the status of vitamin B2 is considered deficient in ≈30% of vegans [31,32].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In fact, nutrients include molecules that constitute DNA and histone methylation, such as methylfolate, choline, betaine, methionine, vitamins B12, B6, and B2 (52). Several studies showed the critical nutrients occurrence for each dietary regime (53)(54)(55)(56). In particular, on the micronutrient level, one study carried out on the largest sample of vegan dieters worldwide reported that the men following a vegan diet have lower intake of saturated fatty acids (SFA), retinol, vitamin B12 and D, calcium, zinc than omnivorous diet.…”
Section: Discussionmentioning
confidence: 99%